Dynamics of Leaders in Indonesia's Environmental Sustainability - Freddy Johanis Rumambi (Publikasi Indonesia, 2024)
Leader dynamics play an important role in promoting environmental sustainability practices within organizations. Effective leaders can inspire and guide communities in preserving their environment. With strong leadership, organizations can move toward sustainability, embrace innovation, and be role models in maintaining a balance between economic growth and environmental preservation. This research analyses the impact of leader dynamics on efforts to preserve a sustainable environment through their role in environment-related decision-making and how leadership styles can affect environmental conservation. This research was conducted using a qualitative approach. Data are obtained from various research results and previous research relevant to the study's content. The results found the importance of leader dynamics in encouraging environmental sustainability practices. Leadership plays an important role in encouraging environmental sustainability practices. Different leadership strategies and interventions towards environmental sustainability practices. Understanding the dynamics of leaders in promoting environmental sustainability is essential to encourage the widespread adoption of sustainable practices in Indonesia